Empowering MSMEs Through Financial Literacy: Exploring Strategies for Sustainable Growth - Alfaira Alfaira; Dyah Palupiningtyas (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
This study examines strategies to increase financial literacy to encourage the growth of MSME financial performance in Semarang Regency. Using a qualitative approach, the study involved 120 MSMEs with data collection through in-depth interviews, observations, and focus group discussions. The results of the study show that the condition of financial literacy is still low, with 65.3% of MSMEs not doing regular financial records, 77.5% mixing business-personal finance, and 81.7% lacking understanding of financial products. Structured mentoring programs with a holistic approach have proven to be effective in increasing the financial management capacity of MSMEs, marked by an increase in turnover (35.2%), operational efficiency (24.7%), and access to capital (19.8%). Multi-stakeholder collaboration and digital technology integration are key factors in the success of the program. The research results in a financial literacy development framework that can be adapted for implementation in other regions.